2023
DOI: 10.1002/bbb.2484
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of process integration approach for coir biosoftening and lignin‐modifying enzyme production from agro residues

Abstract: Lignin present in the inner core of natural lignocellulosic fibers is preferably removed for use in the textile industry as it hinders fiber spinnability. This study focuses on integrating the bioprocessing of agro residues and a natural fiber source (coir) for the effective production of lignin-modifying enzymes while simultaneously softening the natural fibers. The lignin content in the raw fibers (42.17%) could be reduced by 14-31% by treating them with Phanerochaete chrysosporium for 30 days in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Chaga enzymes have also shown potential in the textile and detergent industries. As bio-catalysts, they can be utilized in the processing of natural fibers like cotton and hemp ( Pavithra et al, 2023 ; Asemoloye et al, 2021 reported that by effectively removing lignin and impurities from these fibers, the ligninolytic peroxidase enzyme contributed to the production of cleaner and higher-quality textiles. In the detergent industry, Chaga enzymes were found to enhance the efficiency of laundry detergents by aiding in stain removal and facilitating the degradation of organic matter ( Asemoloye et al, 2021 ).…”
Section: Cosmetic Usesmentioning
confidence: 99%
“…Chaga enzymes have also shown potential in the textile and detergent industries. As bio-catalysts, they can be utilized in the processing of natural fibers like cotton and hemp ( Pavithra et al, 2023 ; Asemoloye et al, 2021 reported that by effectively removing lignin and impurities from these fibers, the ligninolytic peroxidase enzyme contributed to the production of cleaner and higher-quality textiles. In the detergent industry, Chaga enzymes were found to enhance the efficiency of laundry detergents by aiding in stain removal and facilitating the degradation of organic matter ( Asemoloye et al, 2021 ).…”
Section: Cosmetic Usesmentioning
confidence: 99%
“…and short‐chain alcohols with the aid of acid/base catalysts 4,5 . However, the use of alkaline catalysts is suitable only for high‐quality oils with low FFAs and low water content; otherwise, the saponification occurs, resulting in low conversion 6 . Whereas the use of homogeneous acid catalysts for FFAs and low‐quality feedstock is a good idea for producing biodiesel, it is virtually non‐reusability, equipment corrosion, and the generation of more wastewater 7 .…”
Section: Introductionmentioning
confidence: 99%